Multifactorial Analysis of the Parameters for Immunity in Preterm Infants - Aryayev, N.L; Shevchenko, I.M; El Mezewghi, H.M; Shevchenko, N.V (Journal of Diseases, 2017)
The multifactorial analysis of the immunity for the preterm infants, born at 34-36 weeks gestation, has been performed. Three factors of the external load, which were 55.71% of the power load, have been determined with the method of principal components. As a result of the analysis, we can come to the conclusion about the feasibility of the advanced study, the parameters of the immune system for the preterm infants, are as follows: The complement fractions, The circulating immune complexes, T-lymphocytes, T-helper cells, B-lymphocytes, the immunoregulatory index, and IgE.